HUBUNGAN MENGONSUMSI MAKANAN KARIOGENIK DENGAN KEJADIAN KARIES PADA ANAK USIA SEKOLAH DI MI AL-HIDAYAH - Karina Nur Ramadhanintyas (STIKES Bhakti Husada Mulia Madiun, 2020)
Teeth caries common in primary school children are caused by cariogenic food consumption habits. The children like to cousume cariogenik food, because it has a sweet and tasty. Dental caries is a disease of dental hard tissue (email, dentin). Objective of this study was to determine the relationship Cariogenik Consumption Eating Relations With Caries In School Age Children. This study uses correlation design with cross sectional approach. The study population are 105 students in grade I and II, sample 51 students whose teeth have not experienced loose teeth taken by simple random sampling method. The statistical test used the Spearman test.The results of this study showed respondents who frequently consume cariogenic foods as are 28 students (54.9%). Respondents who have dental caries are 37 students (72.5%) and respondents who did not happen dental caries are 14 students (27.5%). Results obtained spearman test p-value = 0.000 so that the alternative hypothesis is accepted. the Conclusion of this study, there is relationship between cariogenik consumption with caries is habits and caries.The from this study that the cariogenic foods can cause dental caries. So less consumption of cariogenic foods (candy, chocolate, ice cream and biscuits) can reduce the number of dental caries in MI AL-Hidayah Madiun.